Process for separating polyarylene sulfide and method for producing polyarylene sulfide resin composition
Patent Information
- Application Number
- CN202280037011.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-19
- Filing Date
- 2022-07-11
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-07-11
AI Technical Summary
PPS虽然通过优异的耐久性而适合材料再循环,但是其多半作为玻璃纤维增强PPS树脂组合物而流通于市场,具有不能作为通用性高的再循环原始资源而有效地利用的课题
[0034]根据本发明,可以从PAS树脂组合物或其成型品,从LCA的观点考虑合理地回收PAS。
Smart Images

Figure BDA0004562978120000041 
Figure BDA0004562978120000051 
Figure BDA0004562978120000052
Abstract
Description
Technical Field
[0001] This invention relates to a method for separating polyarylene sulfides from a polyarylene sulfide resin composition or a molded article thereof, and a method for manufacturing a polyarylene sulfide resin composition. Background Technology
[0002] Polyphenylene sulfide (hereinafter, sometimes abbreviated as PPS) resin is an engineering plastic with excellent heat resistance, chemical resistance, flame retardancy and electrical properties. As a resin composition containing fillers such as glass fiber and carbon fiber and additives such as elastomers, it is mainly used in automotive parts, water supply parts and electrical and electronic parts.
[0003] In recent years, the recycling of thermoplastic resins that have been used and recycled in the market has accelerated in order to realize a circular economy. Although PPS is suitable for material recycling due to its excellent durability, it is mostly circulated in the market as glass fiber reinforced PPS resin compositions, which raises the issue of not being effectively utilized as a highly versatile recycling resource.
[0004] Furthermore, molded products that have been used and recycled in the market have reduced mechanical properties due to the presence of dust and oily dirt. Additionally, during molding and use of the molded products, odors from dirt and mold contamination can occur, limiting their recyclability.
[0005] Therefore, there is a need for a technology that is also excellent from the perspective of life cycle assessment (LCA) due to its low resource consumption and low energy consumption, to separate and recover PPS from PPS resin compositions containing dirt.
[0006] As a method for recovering and reusing resin and fibers from resin compositions, a method is disclosed that uses supercritical or subcritical water to hydrolyze fiber-reinforced plastics, separating the resin and fibers for recovery (e.g., Patent Document 1). Furthermore, a method is disclosed that after depolymerizing polyarylene sulfides by acting alkali metal sulfides, a method is disclosed that separates the resin and fibers for recovery (e.g., Patent Document 2). Additionally, a method is disclosed that after dissolving a blend polymer containing PAS and glass fibers in a solvent, it is redeprecipitated in a liquid medium to recover PAS (e.g., Patent Document 3).
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent Application Publication No. 10-87872 (Claims, Embodiments)
[0010] Patent Document 2: Japanese Patent Application Publication No. 04-007334 (Claims, Embodiments)
[0011] Patent Document 3: Japanese Patent Application Publication No. 11-140221 (Claims, Embodiments) Summary of the Invention
[0012] The problem that the invention aims to solve
[0013] However, the method in Patent Document 1 involves hydrolysis at ultra-high temperatures of 300–500°C, resulting in a high energy load, which is a drawback from the perspective of LCA (Liquid Carbon Acid). Furthermore, there is no disclosure specific to the type of plastic, making it unsuitable for PPS composed of non-hydrolyzable binding groups. The method in Patent Document 2 depolymerizes PAS to an oligomer level in a polar organic solvent, then repolymerizes it for reuse, leading to new resource consumption and energy load, which is also a drawback from the perspective of LCA. Moreover, because PAS oligomers have excellent solubility in polar organic solvents, separation from low-molecular-weight contaminants becomes difficult. The method in Patent Document 3 recovers PAS through reprecipitation, requiring a large amount of solvent, which is also a drawback from the perspective of LCA.
[0014] Methods for solving problems
[0015] To address this issue, the method for separating polyarylene sulfides of the present invention has the following configuration. That is,
[0016] A method for separating polyarylene sulfides (hereinafter, PAS) comprising the following steps 1 to 4.
[0017] Step 1: The step of heating the PAS resin composition or its molded article in an organic polar solvent to a temperature above 200°C and below 400°C to dissolve the PAS and obtain a PAS solution (A).
[0018] Step 2: The process of separating PAS solution (A) into solid and liquid components, namely solid and PAS solution (B).
[0019] Step 3: The process of cooling the PAS solution (B) obtained in Step 2 to a temperature above 20°C and below 200°C to precipitate PAS.
[0020] Step 4: A step to separate PAS by performing solid-liquid separation on the mixture obtained in Step 3.
[0021] The method for separating polyarylene sulfides of the present invention preferably includes, in step 1 above, a PAS resin composition or its molded product containing at least one selected from inorganic fillers and organic fillers.
[0022] The preferred method for separating polyarylene sulfides of the present invention is that the molded product of the PAS resin composition in step 1 above is a molded product that has been recycled after being used as an article.
[0023] The preferred method for separating polyarylene sulfides in this invention uses NMP as the organic polar solvent in step 1 above.
[0024] The separation method of polyarylene sulfides of the present invention is preferably carried out at a temperature of 50°C or higher and 150°C or lower for the precipitation of step 3 described above.
[0025] The preferred method for separating polyarylene sulfides of the present invention is that the weight-average molecular weight (Mw) of the PAS contained in the PAS resin composition or its molded product before dissolution in step 1 is 10,000 or more and 60,000 or less.
[0026] The method for separating polyarylene sulfides of the present invention is preferably carried out in a continuous manner, including some or all of the above steps 1 to 4.
[0027] The separation method of polyarylene sulfides of the present invention preferably reduces the Mw of PAS contained in the PAS resin composition or its molded article before dissolution in step 1 to more than 10,000 and less than 60,000 in step 1.
[0028] The preferred method for separating polyarylene sulfides of the present invention is to add a sulfur compound to the solution in step 1 above.
[0029] The method for separating polyarylene sulfides of the present invention preferably uses at least one of the following sulfur compounds: alkali metal sulfides, alkali metal hydrogen sulfides, and hydrogen sulfide.
[0030] The preferred method for separating polyarylene sulfides of the present invention is to wash and recover the separated PAS after step 4 described above.
[0031] Furthermore, the method for manufacturing the polyarylene sulfide resin composition of the present invention has the following structure. That is,
[0032] A method for manufacturing a PAS resin composition, wherein PAS obtained by the separation method described above, in which the separated PAS is washed and recovered after step 4, is used as a raw material.
[0033] The effects of the invention
[0034] According to the present invention, PAS can be rationally recycled from the PAS resin composition or its molded articles from the viewpoint of LCA. Detailed Implementation
[0035] The PAS resin composition used in this invention or its molded articles contain a homopolymer or copolymer in which repeating units of formula -(Ar-S)- are the main structural units. Here, "as the main structural unit" means that the repeating unit is contained in 80 mol% or more of all structural units constituting PAS. As for Ar, any unit shown in formulas (A) to (K) below can be exemplified, but the unit shown in formula (A) is particularly preferred.
[0036]
[0037] R1 and R2 are substituents selected from hydrogen, alkyl, alkoxy, halogen, and carboxyl groups. R1 and R2 can be the same or different.
[0038] As long as the repeating unit is used as the main structural unit, it can contain a small amount of branched units or crosslinked units as shown in formulas (L) to (N). The copolymerization amount of these branched units or crosslinked units is preferably in the range of 0 to 1 mol% relative to 1 mole of the -(Ar-S)- unit.
[0039]
[0040] As a repeating unit of PAS, it is preferable to contain 90 mol% or more of the para-aryl sulfide unit of formula (A), more preferably 95 mol% or more, and even more preferably 98 mol% or more. If the para-aryl sulfide unit is less than 90 mol%, that is, if there are more ortho-aryl sulfide units and meta-aryl sulfide units, then there is a tendency for the high melting point and mechanical properties inherent in PAS to decrease.
[0041] Representative materials of these PAS include random copolymers, block copolymers, and mixtures thereof of polyphenylene sulfide, polyphenylene sulfide sulfone, polyphenylene sulfide ether, and polyphenylene sulfide ketone. Particularly preferred PAS include polyphenylene sulfide (hereinafter, PPS) containing 90 mol% or more, preferably 95 mol% or more, and more preferably 98 mol% or more of p-phenylene sulfide units as the main structural unit of the polymer.
[0042]
[0043] Regarding the method of manufacturing PAS, PAS can be obtained using known methods such as desalting and polycondensing a dihaloaromatic compound with a sulfurizing agent in an organic polar solvent, or synthesizing PAS using diiodobenzene and sulfur under molten conditions. When molding articles are made using PAS resin compositions, due to the requirement of excellent heat resistance and chemical resistance, the melting point of the PAS contained in the PAS resin composition or its molded article is preferably 230°C or higher and less than 320°C. For PPS with arylene units as phenylene units, the lower limit of the typical melting point is 250°C or higher and the upper limit is less than 300°C. From the viewpoint of strength and toughness, the weight-average molecular weight of PAS is preferably 10,000 or higher, more preferably 15,000 or higher. Particularly from the viewpoint of reducing solubility in organic polar solvents and improving separability from low molecular weight components such as dirt, a weight-average molecular weight of 20,000 or higher is even more preferred. On the other hand, in step 1, which dissolves the PAS resin composition or its molded article of the present invention in an organic polar solvent, if the molecular weight of PAS is too high, it is difficult to dissolve in the organic polar solvent, resulting in reduced recovery efficiency. Therefore, the weight-average molecular weight of PAS contained in the PAS resin composition or its molded article is preferably less than 200,000, more preferably less than 100,000. In particular, from the viewpoint of reducing energy load by lowering the heating temperature through improved solubility in organic polar solvents, it is further preferred to be less than 80,000, and particularly preferably less than 60,000.
[0044] The following sections describe the PAS resin composition, the molded article, the organic polar solvent, process 1, process 2, process 3, process 4, and the recycled materials in sequence.
[0045] [PAS Resin Composition]
[0046] PAS resin composition is obtained by mixing fillers and other additives into PAS, heating it above the melting point of PAS, and then performing melt mixing. In order to achieve excellent performance, inorganic fillers and organic fillers are generally used as fillers.
[0047] Examples of inorganic filler materials include glass fiber, glass abrasive fiber, carbon fiber, potassium titanate whiskers, zinc oxide whiskers, calcium carbonate whiskers, wollastonite whiskers, aluminum borate whiskers, alumina fiber, silicon carbide fiber, ceramic fiber, gypsum fiber, metal fiber, basalt fiber, and other fibrous inorganic filler materials; and non-fibrous inorganic filler materials such as talc, wollastonite, zeolite, sericite, mica, kaolin, clay, mica, ferrite, pyrophyllite, bentonite, aluminum silicate, silicon oxide, magnesium oxide, aluminum oxide, zirconium oxide, titanium oxide, iron oxide, magnesium oxide, calcium carbonate, magnesium carbonate, dolomite, calcium sulfate, barium sulfate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, glass beads, glass flakes, glass powder, ceramic beads, boron nitride, silicon nitride, silicon carbide, aluminum silicate, calcium silicate, silicon dioxide, graphite, carbon black, and graphite.
[0048] Examples of organic filler materials include fibrous organic fillers such as polyethylene fiber, polypropylene fiber, polyester fiber, polyamide fiber, polyaramid fiber, fluoropolymer fiber, thermosetting resin fiber, epoxy resin fiber, polyvinylidene 1,1-dichloroethylene fiber, polyvinylidene 1,1-difluoroethylene fiber, and cellulose fiber; and non-fibrous organic fillers such as hard adhesive powder, cork powder, and wood flour.
[0049] These filler materials can be used after pretreatment with coupling agents such as isocyanate compounds, organosilane compounds, organotitanate compounds, organoborane compounds, and epoxy compounds. Additionally, sizing agents can be used.
[0050] PAS resin compositions for purposes such as toughness improvement generally use olefin copolymer resins, including olefin copolymer resins having at least one functional group selected from epoxy, carboxyl, anhydride, amino, hydroxyl and mercapto groups, and olefin copolymers not having the above functional groups.
[0051] For PAS resin compositions, additives can be used for modification of other properties, such as resins other than olefin copolymers, including polyamide, polyethersulfone, polysulfone, polyarylsulfone, polyetherimide, polyphenylene ether, fluorinated resins, and polyetheretherketone; coupling agents such as epoxy compounds, amine compounds, isocyanate compounds, and anhydride compounds; antioxidants such as phenolic and phosphorus-based compounds; color-preventing agents such as hypophosphite; nucleating agents such as talc, kaolin, organophosphorus compounds, and polyetheretherketone; release agents such as ethylenediamine / stearic acid / sebacic acid condensates and organosilicon compounds; flame retardants such as phosphorus-based, bromine-based, and organosilicon compounds; and blackening agents such as carbon.
[0052] [Molded articles of PAS resin composition]
[0053] For various components in automobiles, electrical and electronic products, and housing supply, PAS resin compositions are molded into desired shapes through injection molding, extrusion molding, compression molding, etc. Various molding methods are employed when molding these articles, including molding the resin alone, insert molding combining the resin with metals, and two-color molding combining the resin with other resins. The articles used in this invention are not particularly limited to these molding methods. Furthermore, articles using various joining methods, such as laser welding, hot plate welding, IR welding, vibration welding, and bonding with adhesives, can also be used. In addition to the articles obtained by the above molding processes, fibers, films, and composites thereof made of PAS can also be used.
[0054] The molded articles used in this invention can be defective molded articles, non-standard molded articles, end-material molded articles from injection ports / runners, etc., generated during molding. Other polymers such as polyolefins and PET generated during purging when changing raw materials can also be incorporated. Furthermore, from the viewpoint of realizing a circular economy, molded articles that have been used in the market and then recycled are preferred. Appropriate sorting and washing of molded articles recycled from the market are also preferred. Although molded articles recycled from the market may have adhering oil and dirt, this invention allows for reasonable separation from these contaminants from the perspective of LCA (Liquid Activated Carbon) separation.
[0055] These molded articles are preferably miniaturized to improve the efficiency of sorting and washing, and to enhance their solubility in organic polar solvents during step 1. Examples of miniaturization methods include compression crushing, impact crushing, shear crushing, cutter crushing, mill crushing, and cutting; there are no particular limitations as long as the purpose of this invention is achieved. The size of the miniature articles is preferably 50 mm or less, and 20 mm or less is more preferable from the viewpoint of solubility. Furthermore, the miniaturized molded articles can also be melt-blended and granulated using known methods such as an extruder.
[0056] [Organic polar solvents]
[0057] As an organic polar solvent for dissolving PAS resin compositions or their molded articles, N-alkylpyrrolidones such as N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone; caprolactams such as N-methyl-ε-caprolactam; aprotic organic solvents such as 1,3-dimethyl-2-imidazolium ketone, N,N-dimethylacetamide, N,N-dimethylformamide, hexamethylphosphoric triamine, dimethyl sulfone, and tetramethylene sulfoxide; and mixtures thereof are preferred. Among these, N-methyl-2-pyrrolidone (hereinafter, NMP) is preferred from the viewpoints of easily controlling solubility through the weight-average molecular weight of PAS and its miscibility with water.
[0058] [Process 1]
[0059] In step 1, the PAS resin composition or its molded article is heated in an organic polar solvent to a temperature of 200°C or higher and less than 400°C to dissolve the PAS and obtain a PAS solution (A). From the viewpoint of ensuring sufficient dissolution of PAS and thus improving the PAS recovery rate, a temperature of 220°C or higher is preferred, and more preferably 240°C or higher. Furthermore, from the viewpoint of energy conservation, a temperature of less than 300°C is preferred, and more preferably less than 270°C, which is below the melting point of PAS.
[0060] The weight ratio of the PAS resin composition or its molded article to the organic polar solvent in step 1 cannot be generalized because it depends on the type of organic polar solvent and the weight-average molecular weight of PAS. However, for every 1 kg of organic polar solvent, the weight of PPS contained in the PAS resin composition or its molded article is preferably 20 g or more, more preferably 50 g or more, and from the viewpoint of maximizing production efficiency, it is even more preferably 100 g or more. The upper limit is preferably 500 g or less, more preferably 300 g or less, and from the viewpoint of ensuring sufficient dissolution of PAS, it is even more preferably 200 g or less, and particularly preferably 150 g or less.
[0061] Regarding the heating time for dissolving the PAS resin composition or its molded article in step 1, there is no particular limitation as long as the PAS resin composition or its molded article is dissolved; examples include 5 minutes or more and 5 hours or less. From the viewpoint of productivity and LCA, the upper limit is preferably 3 hours or less, more preferably 2 hours or less, and even more preferably 1 hour or less.
[0062] The process for step 1 can employ various known reaction methods, such as batch and continuous processes. For example, in the case of a batch process, examples include autoclaves and vertical / horizontal reactors, all equipped with a mixer and heating function. In the case of a continuous process, examples include extruders, flow reactors (e.g., flow reactors described in International Publication No. 2019 / 031435), tubular reactors, tubular mixers, vertical / horizontal reactors, and towers, all equipped with heating function. In the case of a batch process, in addition to the aforementioned heating time, a temperature rise time becomes necessary; therefore, from the viewpoint of productivity and LCA (Limited Capacity of Reactors), a continuous process is preferred.
[0063] The PAS resin composition or its molded product is dissolved using the preferred temperature, weight ratio, and heating time. To optimize the separation efficiency of steps 2-4 and achieve both PAS recovery and separation performance, the weight-average molecular weight of the PAS is preferably within an appropriate range, with a lower limit preferably of 10,000 or more, more preferably 20,000 or more, and even more preferably 30,000 or more. The upper limit is preferably 60,000 or less.
[0064] In order to achieve both high yield and separability of recovered PPS, it is also a preferred approach to reduce the weight-average molecular weight of PAS to the above-mentioned preferred range when dissolving the PAS resin composition or its molded article in an organic polar solvent in step 1.
[0065] As a method for reducing the molecular weight of PAS, it is preferable to add a sulfur compound to a solution in which the PAS resin composition or its molded article is dissolved. As the sulfur compound, it is preferable to use at least one compound selected from alkali metal sulfides, alkali metal hydrogen sulfides, and hydrogen sulfide.
[0066] Specific examples of alkali metal sulfides include lithium sulfide, sodium sulfide, potassium sulfide, rubidium sulfide, cesium sulfide, and mixtures of two or more thereof, with lithium sulfide and / or sodium sulfide being preferred, and sodium sulfide being more preferred. These alkali metal sulfides can be used as hydrates or aqueous mixtures, or as anhydrous solutions. It should be noted that an aqueous mixture refers to an aqueous solution, or a mixture of an aqueous solution and a solid component, or a mixture of water and a solid component. Since readily available and inexpensive alkali metal sulfides are generally hydrates or aqueous mixtures, these forms of alkali metal sulfides are preferred.
[0067] Specific examples of alkali metal hydrosulfides include, for example, lithium hydrosulfide, sodium hydrosulfide, potassium hydrosulfide, lithium hydrosulfide, rubidium hydrosulfide, cesium hydrosulfide, and mixtures of two or more thereof, wherein lithium hydrosulfide and / or sodium hydrosulfide are preferred, and sodium hydrosulfide is more preferred.
[0068] Alternatively, alkali metal sulfides prepared by reacting alkali metal hydrogen sulfides with alkali metal hydroxides in a reaction system can also be used. Furthermore, alkali metal sulfides prepared by pre-contaminating alkali metal hydrogen sulfides with alkali metal hydroxides can also be used. These alkali metal hydrogen sulfides and alkali metal hydroxides can be used as hydrates or aqueous mixtures, or as anhydrous forms; hydrates or aqueous mixtures are preferred from the viewpoints of ease of acquisition and cost.
[0069] Furthermore, alkali metal sulfides prepared by reacting alkali metal hydroxides such as lithium hydroxide and sodium hydroxide with hydrogen sulfide in a reaction system can also be used. Alternatively, alkali metal sulfides prepared by pre-contaminating alkali metal hydroxides such as lithium hydroxide and sodium hydroxide with hydrogen sulfide can also be used.
[0070] Regarding the amount of sulfur compound used, for every 1.0 mole of PAS, the sulfur content is preferably 0.01 mol% or more, more preferably 0.1 mol% or more, and even more preferably 1.0 mol% or more. The upper limit is preferably 50 mol% or less, more preferably 10 mol% or less. By reacting the sulfur compound at such a low concentration, the weight-average molecular weight of PAS will not decrease excessively under the dissolution conditions of step 1, and can be adjusted to a preferred range. If it is 0.01 mol% or more, it will not be too diluted, and the molecular weight of PAS can be adjusted efficiently. By keeping the amount of sulfur compound used at 50 mol% or less, excessive depolymerization can be suppressed. It should be noted that the PAS content contained in the PAS resin composition and its molded article is the value obtained by subtracting the amount of filler, elastomer, and other compounding agents from the PAS resin composition and its molded article.
[0071] Furthermore, regarding the amount of alkali metal hydroxide used when the sulfur compound is an alkali metal hydrogen sulfide, it is preferable that per mole of sulfur content in the alkali metal hydrogen sulfide, the amount of hydroxide ions in the alkali metal hydroxide is in the range of 0.95 mol or more and 2.5 mol or less. If this preferred range is met, it is less likely to generate thermally unstable low-molecular-weight PAS, and on the other hand, it is less likely to generate low-molecular-weight PAS with many impurities. Therefore, as a lower limit, per mole of sulfur content in the alkali metal hydrogen sulfide, the amount of hydroxide ions in the alkali metal hydroxide is preferably 1.0 mol or more, more preferably 1.1 mol or more. As an upper limit, it is preferably 2.0 mol or less, more preferably 1.8 mol or less.
[0072] From the viewpoint of improving solubility in organic polar solvents and thus increasing productivity, the crystallinity of the PAS resin composition or its molded product in step 1 is preferably 30% or less, more preferably 20% or less, and even more preferably 10% or less. To obtain a PAS resin composition with such crystallinity, a specific example is to perform a rapid cooling and annealing treatment on the filament obtained by melt-blending the PAS resin composition or its molded product using an extruder or the like before step 1. It should be noted that the crystallinity here is a percentage (%) calculated by subtracting the heat of cold crystallization (J / g) from the heat of fusion of PAS detected when heating from 0°C to 340°C at a rate of 20°C / min using a differential scanning calorimeter, and dividing this value by the heat of complete crystallization of PAS (146.2 (J / g) in the case of PPS).
[0073] [Process 2]
[0074] In step 2 of this invention, the PAS solution (A) obtained in step 1 is separated into a solid and a PAS solution (B) that are insoluble components. There are no particular limitations on the method for solid-liquid separation; known methods can be used, such as pressure filtration using a filter, reduced pressure filtration, sedimentation separation based on the specific gravity difference between the solid and the solution, centrifugation, or methods that further combine them. Decantation separation, which involves precipitation before filtration, is also a preferred method.
[0075] The solids separated in step 2 can include, for example, inorganic fillers, organic fillers, olefin copolymer resins, PAS and other components that have become insoluble through oxidative crosslinking, metals, dust, rust, etc.
[0076] The solid-liquid separation temperature in step 2 is preferably 200°C or higher and less than 400°C, similar to that in step 1. From a production point of view, it is preferably the same as or higher than the heating temperature in step 1. From the viewpoint of fully dissolving PAS and improving PAS recovery rate, it is more preferably 220°C or higher, and even more preferably 240°C or higher. Furthermore, from the viewpoint of energy saving, it is more preferably less than 300°C, and even more preferably less than 270°C, which is below the melting point of PAS. On the other hand, a supercooled state can also be used to suppress the precipitation of PAS from the PAS solution (A) while performing solid-liquid separation treatment below the heating temperature of step 1. In this case, the solid-liquid separation treatment temperature is preferably 100°C or higher, and more preferably 150°C or higher from the perspective of balancing solubility.
[0077] From the viewpoint of suppressing the oxidative crosslinking and modification of PAS, the solid-liquid separation in step 2 is preferably carried out under a non-oxidizing atmosphere. Examples of preferred non-oxidizing atmospheres include inert gases such as nitrogen, helium, and argon. In particular, in step 1, when the weight-average molecular weight of PAS is adjusted using sulfur compounds, the ends of PAS become thiolate structures easily affected by oxidation. Therefore, solid-liquid separation under a non-oxidizing atmosphere is effective in maintaining the high quality of the recovered PAS.
[0078] In the case of a batch process for step 2, examples include a process where a filter is connected to the lower part of the discharge from the batch dissolving tank, the dissolved liquid is discharged from the batch dissolving tank for recovery, and filtration is performed using a filter in other steps. Furthermore, in the case of a continuous process, examples include a process where a filter is installed midway through a continuous dissolving unit such as a flow reactor, and a process where a decanter-type continuous centrifuge is used after the continuous dissolving unit for sedimentation and filtration separation. The packing material and other residues accumulated in these filters can be recovered in both batch and continuous processes.
[0079] Furthermore, recovering the filler material separated in step 2 is preferred from the viewpoint of efficient utilization of raw materials. As the filler material, it is preferable to recover at least one selected from inorganic and organic fillers. Since the inorganic and organic fillers recovered in step 2 through solid-liquid separation have a solution containing PAS and organic solvent adhering to their surface, examples include heating the filler material with PAS and organic polar solvent adhering to a high temperature of approximately 500°C to volatilize / burn the organic matter and recover the filler material, or washing it with a solvent compatible with the organic polar solvent used in step 1 to recover the filler material. There are no particular limitations on the washing conditions; it is sufficient to appropriately set the washing volume, number of washes, and washing temperature to remove PAS and organic polar solvent from the inorganic and organic fillers. Additionally, after washing with the organic polar solvent, appropriate replacement with water or the like can be performed.
[0080] [Process 3]
[0081] In step 3 of the present invention, the PAS solution (B) obtained in step 2 is cooled to 20°C or higher and 200°C or lower to precipitate PAS. From step 1 to step 3, solid-liquid separation is performed by varying the temperature in stages in the same organic polar solvent, thereby enabling reasonable recovery of PAS from PPS resin compositions or their molded articles containing dirt, etc., from the viewpoint of LCA.
[0082] The precipitation temperature in step 3 is preferably adjusted based on the components other than PAS contained in the PAS solution (B). Higher precipitation temperatures result in a greater amount of components dissolved in the organic polar solvent, thus improving the separability of PAS. However, this also means that low-molecular-weight PAS cannot be recovered, leading to a lower recovery rate. From the viewpoint of separating fouling components, low-molecular-weight components such as olefin copolymer resins, the precipitation temperature is preferably 50°C or higher, and more preferably 100°C or higher from the viewpoint of separating oligomers derived from PAS. By improving the separability of low-molecular-weight components, the generation of gases during the melt processing of the recovered PAS is suppressed, which can improve the quality of materials such as membranes and fibers, or suppress mold fouling during molding. Furthermore, from the viewpoint of improving the PAS recovery rate, the upper limit of the precipitation temperature is more preferably 150°C or lower.
[0083] As long as the temperature range mentioned above is within step 3, both the recovery rate and the separation properties of PAS can be achieved. By adopting any of the following methods, such as cooling at a certain temperature, gradually lowering the temperature, or continuously lowering the temperature, the cooling rate can be controlled to adjust the particle size of the obtained PAS particles.
[0084] As long as the temperature range mentioned above is maintained in step 3, it is possible to achieve both PAS recovery rate and separation efficiency. Adding substances that improve the PAS precipitation efficiency, and water is preferred from the perspective of LCA and cost.
[0085] Regarding the precipitation time in step 3, there are no particular restrictions as long as PAS is precipitated from the PAS solution (B), and examples include 5 minutes or more and 24 hours or less. From the viewpoint of productivity and LCA, the upper limit is preferably 12 hours or less, and more preferably 6 hours or less.
[0086] The process for step 3 can employ various known reaction methods, such as batch and continuous processes. For example, if it is a batch process, examples include autoclaves, vertical / horizontal reactors, and tanks, all of which have agitator and heating functions. If it is a continuous process, examples include extruders, flow reactors, tubular reactors, pipe mixers, vertical / horizontal reactors, and towers, all of which have heating functions.
[0087] [Process 4]
[0088] In step 4 of this invention, the mixture containing precipitated PAS obtained in step 3 is separated into PAS and an organic polar solvent containing impurities. There are no particular limitations on the method for solid-liquid separation; known methods can be used, such as pressure filtration using a filter, reduced pressure filtration, sedimentation separation using the difference in specific gravity between the solid components and the solution, centrifugation, and further combining the components. Decantation separation, which involves precipitation before filtration, is also a preferred method.
[0089] The solid-liquid separation temperature of step 4 is preferably 20°C or higher and 200°C or lower, just like in step 3. From a production point of view, it is preferable to use the same temperature as the precipitation temperature of step 3. On the other hand, a supercooled state can also be used to perform solid-liquid separation below the precipitation temperature of step 3 while suppressing the precipitation of components other than PAS from the mixture obtained in step 3.
[0090] In step 4, to improve the operability of the mixture while washing PAS, it is preferable to add a suitable washing solvent. While there are no particular limitations on the washing solvent, washing with an organic solvent presents the problem that the oligomer components contained in PAS are removed, thus reducing the yield of recovered PAS. From the viewpoint of efficiently recovering PAS, washing with water is preferred. There are no particular limitations on the washing conditions using water; as long as the amount of water, the number of washes, and the washing temperature are appropriately set to remove organic polar solvents from PAS, it is acceptable. Especially when the weight-average molecular weight of PAS is adjusted by adding a sulfur compound in step 1, washing with water is preferred from the viewpoint of washing away reaction products such as salts. The washing solvent can be added either before or after the solid-liquid separation of the mixture obtained in step 3.
[0091] [Recyclables]
[0092] The PAS recovered in this invention can be reinvested in resources through repolymerization or other means, or reused without consuming a large amount of energy. By processing PAS into films, fibers, or resins, or by melt-blending PAS with compounding materials, it can be recycled as PAS resin compositions and their molded products. It is expected to be used as an environmental material in various applications such as automotive, electrical and electronic, and housing supply. Furthermore, in order to achieve sufficient physical properties in these applications, the weight-average molecular weight of the recovered PAS is preferably 10,000 or more and 60,000 or less, more preferably 20,000 or more.
[0093] In this invention, the recovered PAS can be recycled together with the recovered low molecular weight PAS using dihaloaromatic compounds and sulfide compounds as raw materials to produce high molecular weight PAS and thus be recycled, provided that there are no problems from the LCA point of view.
[0094] Furthermore, the inorganic and organic filler materials separated and recovered in step 2 of the present invention can also be reused as filler materials for various resin compositions.
[0095] Example
[0096] The method of the present invention will be further described in detail below through examples and comparative examples, but the present invention is not limited to these examples. It should be noted that various measurement methods are described below.
[0097] (1) Analysis of weight-average molecular weight
[0098] The weight-average molecular weight (Mw) was calculated in polystyrene form by gel permeation chromatography (GPC). The determination conditions for GPC are shown below.
[0099] Device: SSC-7100 (Scientology Co., Ltd.)
[0100] Column name: GPC3506 (Scientology Co., Ltd.)
[0101] Eluent: 1-Chloronaphthalene
[0102] Detector: Differential refractive index detector
[0103] Column temperature, detector temperature: 210℃
[0104] Flow rate: 1.0 mL / min
[0105] Sample concentration: 0.2% by weight (solvent: 1-chloronaphthalene)
[0106] (2) Amount of gas produced
[0107] The recycled PPS obtained through the various examples and comparative examples was weighed in an aluminum cup (10g), and treated in an Espec Corporation PHH202 hot air dryer heated to 320°C for 2 hours, then cooled to room temperature. Next, the weight was measured, and the weight reduction rate (%), which is the ratio of the weight change before and after drying to the weight before drying, was calculated and set as the amount of gas generated.
[0108] (3) Mechanical properties
[0109] Regarding the ISO(1A) dumbbell test piece, the tensile properties were evaluated at 23°C using an Autograf AG-Xplus20kN tester, according to ISO527-1(2012) and ISO527-2(2012), with a support distance of 114 mm and a tensile speed of 5 mm / min.
[0110] Next, the bending characteristics were evaluated according to ISO 178 (2010) under the conditions of a distance of 64 mm between the supports and a speed of 2 mm / min.
[0111] Next, the test piece obtained by cutting the ISO(1A) dumbbell was evaluated according to ISO179(2010) for its notched impact strength.
[0112] [Reference Example 1] Modulation of PPS-1
[0113] In a 70L autoclave equipped with a stirrer and a bottom stopper valve, 8.3 kg (70.0 mol) of 47.5% sodium hydrosulfide, 2.9 kg (69.8 mol) of 96% sodium hydroxide, 11.5 kg (115.5 mol) of N-methyl-2-pyrrolidone (NMP), 1.9 kg (23.1 mol) of sodium acetate, and 10.5 kg of deionized water were added. The mixture was slowly heated to 245°C for approximately 3 hours while nitrogen was introduced at atmospheric pressure. After distilling off 14.8 kg of water and 0.3 kg of NMP, the reaction vessel was cooled to 200°C. Regarding the amount of hydrogen sulfide escaping, 0.02 mol of alkali metal sulfide was added per mol.
[0114] Then, 10.5 kg (71.1 mol) of p-dichlorobenzene and 9.4 kg (94.5 mol) of NMP were added. The reaction vessel was sealed under nitrogen atmosphere, and the temperature was increased from 200 °C to 270 °C at a rate of 0.6 °C / min while stirring at 240 rpm. After reacting at 270 °C for 100 minutes, the bottom valve of the autoclave was opened, and the contents were flash-evaporated into a vessel equipped with a stirrer while pressurizing with nitrogen atmosphere. Most of the NMP was removed at 250 °C.
[0115] The obtained solid material and 76 L of ion-exchanged water were added to an autoclave equipped with a stirrer and washed at 70°C for 30 minutes, followed by vacuum filtration using a glass filter. Then, 76 L of ion-exchanged water heated to 70°C was injected into the glass filter, and vacuum filtration was performed to obtain a filter cake.
[0116] The resulting filter cake and 90 L of deionized water were added to an autoclave equipped with a stirrer. Acetic acid was added to bring the pH to 7, and the temperature was raised to 195 °C and maintained for 30 minutes. The mixture was then filtered through a glass filter, and the recovered filter cake was dried at 120 °C under a nitrogen atmosphere to obtain dried PPS (PPS-1) with a weight average molecular weight of 42,000.
[0117] [Reference Example 2] Molded article of PPS resin composition (PPS-2)
[0118] 160 parts by weight of PPS-1 were fed into the main feed section of a TEX30α twin-screw extruder (L / D=30) manufactured by Nippon Steel Co., Ltd. 40 parts by weight of glass fiber (T-747H manufactured by Denki Glass Co., Ltd., with an average fiber diameter of 10.5 μm) were further fed into the side feed section of the same twin-screw extruder. The mixture was melt-blended at 320°C and 200 rpm. Particles were pelletized to a length of 10 mm or less using a filament pelletizer and dried at 120°C to obtain a PPS resin composition. The obtained PPS resin composition was then injection molded using a Sumitomo Heavy Industries SE75DUZ-C250 injection molding machine at a resin temperature of 310°C and a mold temperature of 130°C to produce ISO(1A) dumbbell-shaped molded products (PPS-2).
[0119] [Example 1]
[0120] A 1L autoclave equipped with a bottom stop valve and a high-temperature filter (using a 1μm PTFE filter) directly connected below the bottom stop valve for nitrogen pressurization were prepared. 10g of PPS-2 and 300g of NMP (20g of organic polar solvent per kg of PPS) were added to the autoclave. After nitrogen purging, the temperature was raised to 250°C for 60 minutes and maintained for 60 minutes to obtain a PPS solution (A) (Step 1). Then, the bottom stop valve of the autoclave was opened, and the solution was transferred to a 250°C high-temperature filter. The filter was pressurized with nitrogen to 0.2MPa, and pressure filtration was performed at 250°C under a non-oxidizing atmosphere to separate the PPS solution (B) from the glass fiber (Step 2). The resulting PPS solution (B) was cooled to 75°C to precipitate PPS (Step 3). Then, it was added to 5L of ion-exchange water and filtered using a filter with a 10–16μm sieve. The resulting filter cake was subjected to the same washing and filtration process three times at 75°C, and then dried at 120°C to obtain recovered PPS. The recovery rate was determined from the weight of the recovered PPS and the weight of PPS added to PPS-2. Furthermore, the weight-average molecular weight of the recovered PPS and the amount of gas produced were determined using the above method.
[0121] [Examples 2-9]
[0122] The weight of PPS per 1 kg of organic polar solvent and the precipitation temperature of step 3 were changed, but otherwise, recovered PPS was obtained by operating in the same manner as in Example 1.
[0123] [Comparative Example 1] (The method described in Patent Document 3)
[0124] Instead of an organic polar solvent, 300 g of 1-chloronaphthalene (1-CN) was added to an autoclave, and steps 1 and 2 were performed in the same manner as in Example 1. The resulting PPS solution (B) at 250°C was added to 5 L of acetone to precipitate PPS, which was then filtered through a filter with a sieve aperture of 10–16 μm. The resulting filter cake was washed and filtered three times with acetone at 30°C, and then dried at 120°C to obtain recovered PPS.
[0125] [Comparative Example 2] (The method described in Patent Document 3)
[0126] The weight of PPS per 1 kg of solvent was changed, but otherwise, recovered PPS was obtained by the same procedure as in Comparative Example 1.
[0127] The conditions and characteristics of PPS recycling in the examples and comparative examples are shown in Table 1.
[0128] [Table 1]
[0129]
[0130] The following situation was clarified by comparing the embodiments and comparative examples in Table 1 above.
[0131] In Example 1, it was demonstrated that by dissolving the PPS resin composition in the organic polar solvent NMP and filtering it at high temperature, the same amount of PAS as before dissolution could be recovered. Furthermore, since the organic polar solvent is soluble in water, PAS can be easily recovered with minimal loss during recovery, resulting in a high recovery rate. On the other hand, as shown in Comparative Example 1, if PAS is dissolved in a water-insoluble solvent such as 1-chloronaphthalene (not an organic polar solvent), it is known that an organic solvent such as acetone is needed to remove the 1-chloronaphthalene during PAS recovery, leading to the dissolution and removal of a portion of the PAS, thus reducing the PAS recovery rate. Moreover, the amount of organic solvent used is significantly greater than in Example 1, which is disadvantageous from the viewpoint of LCA (Liquid Acid Reduction).
[0132] Furthermore, in Examples 4-9, although the PPS recovery rate decreased by changing the precipitation temperature of step 3, the oligomer components of PPS, which could contribute to gas and mold contamination during melt processing, were dissolved and removed by the organic polar solvent. Therefore, similar to Comparative Example 2, the weight reduction rate of the recovered PPS was low. If the recovery rate and quality of the recovered PPS are equivalent in the Examples and Comparative Examples, then the superior examples are effective separation methods from the viewpoint of LCA.
[0133] [Reference Example 3] Modulation of PPS-3
[0134] In a 70L autoclave equipped with a stirrer and a bottom stopper valve, 8.27 kg (70.00 mol) of 47.5% sodium hydrosulfide, 2.94 kg (70.63 mol) of 96% sodium hydroxide, 11.45 kg (115.50 mol) of N-methyl-2-pyrrolidone (NMP), 2.24 kg (27.3 mol) of sodium acetate, and 5.50 kg of deionized water were added. The mixture was slowly heated to 245°C for approximately 3 hours while nitrogen was introduced at atmospheric pressure. After distilling off 9.77 kg of water and 0.28 kg of NMP, the reaction vessel was cooled to 200°C. The residual water content in the system per 1 mol of alkali metal sulfide added, including water consumed by the hydrolysis of NMP, was 1.06 mol. Furthermore, the amount of hydrogen sulfide escaping was 0.02 mol per 1 mol of alkali metal sulfide added.
[0135] The mixture was then cooled to 200°C, and 10.32 kg (70.20 mol) of p-dichlorobenzene and 9.37 kg (94.50 mol) of NMP were added. The reaction vessel was sealed under nitrogen atmosphere, and the temperature was increased from 200°C to 235°C at a rate of 0.8°C / min while stirring at 240 rpm. The reaction was carried out at 235°C for 40 minutes. Then, the temperature was increased to 270°C at a rate of 0.8°C / min, and the reaction was carried out at 270°C for 70 minutes. Then, 2.40 kg (133 mol) of water was injected while cooling from 270°C to 250°C over 15 minutes. The mixture was then slowly cooled from 250°C to 220°C over 75 minutes, and then rapidly cooled to near room temperature before the contents were removed.
[0136] The contents were diluted with approximately 35 L of NMP to form a slurry. After stirring at 85°C for 30 minutes, the slurry was filtered through an 80-mesh metal screen (0.175 mm aperture) to obtain a solid. The obtained solid was similarly washed and filtered with approximately 35 L of NMP. The obtained solid was diluted with 70 L of deionized water, stirred at 70°C for 30 minutes, and then filtered through an 80-mesh metal screen to recover the solid. This operation was repeated a total of 3 times. The obtained solid and 32 g of acetic acid were diluted with 70 L of deionized water, stirred at 70°C for 30 minutes, and then filtered through an 80-mesh metal screen. The obtained solid was further diluted with 70 L of deionized water, stirred at 70°C for 30 minutes, and then filtered through an 80-mesh metal screen to recover the solid. The solid obtained in this way was dried at 120°C under a nitrogen atmosphere to obtain dried PPS (PPS-3) with a weight average molecular weight of 73,000.
[0137] [Reference Example 4] Molded article of PPS resin composition (PPS-4)
[0138] PPS-3 was used instead of PPS-1. Otherwise, the same molded product of ASTM No. 1 dumbbell (PPS-4) was produced in the same way as PPS-2.
[0139] [Example 10]
[0140] A 1L autoclave equipped with a bottom stop valve and a high-temperature filter (using a 1μm PTFE filter) directly connected below the bottom stop valve for nitrogen pressurization were prepared. 450g of PPS and 300g of NMP (100g of organic polar solvent per kg of PPS) were added to the autoclave. After nitrogen purging, the temperature was raised to 250°C and maintained for 1 hour to obtain a PPS solution (A) (Step 1). Then, the bottom stop valve of the autoclave was opened, and the solution was transferred to a 250°C high-temperature filter. The filter was pressurized to 0.2MPa with nitrogen, and pressure filtered under a non-oxidizing atmosphere at 250°C to separate the PPS solution (B) from the glass fiber (Step 2). The resulting PPS solution (B) was cooled to 150°C to precipitate PPS (Step 3). Then, it was added to 5L of ion-exchange water and filtered using a filter with a 10–16μm sieve. The resulting filter cake was subjected to the same washing and filtration process three times at 75°C, and then dried at 120°C to obtain recovered PPS. The recovery rate was determined from the weight of the recovered PPS and the weight of PPS added to PPS-2. Furthermore, the weight-average molecular weight and weight reduction rate of the recovered PPS were determined using the above method. In addition, to analyze the weight-average molecular weight of the PPS after step 1, a PTFE filter was not used in the high-temperature filter, thus determining the weight-average molecular weight of the PAS solution (A) that was transferred without solid-liquid separation in step 2.
[0141] [Example 11]
[0142] The heating temperature of step 1 was changed to 280°C, and PPS was recovered through the same operation as in Example 10.
[0143] [Example 12]
[0144] Before step 1, PPS-4 was fed into a TEX30α twin-screw extruder (L / D=30) manufactured by Nippon Steel Co., Ltd. The filament obtained by melt mixing at 320°C and 200 rpm was quenched in a water bath and then pelletized to a length of less than 10 mm using a filament pelletizer. Otherwise, recycled PPS was obtained through the same operation as in Example 10.
[0145] [Example 13]
[0146] In addition to PPS-4 and NMP, 0.73g of a compound prepared in advance by heating 114.0g of 48% sodium hydrosulfide (NaSH), 39.8g of NaOH and 163.6g of NMP to above 120°C to react with the raw materials used in step 1 were also added. Otherwise, PPS was recovered by the same operation as in Example 10.
[0147] The conditions and characteristics of PPS recycling in the examples are shown in Table 2.
[0148] [Table 2]
[0149]
[0150] The following situation was clarified by comparing the embodiments in Table 2 above.
[0151] A comparison of Examples 8 and 10 shows that the weight-average molecular weight of PPS in the PPS resin composition or molded article increases, thereby reducing the recovery rate of PPS. High molecular weight PPS, which is insoluble in organic polar solvents under the dissolution conditions of Step 1, exists as a solid and is separated in Step 2. It is evident that increasing the heating temperature of Step 1 as shown in Example 11, reducing the crystallinity of PPS as shown in Example 12, and adding sulfur compounds to reduce the molecular weight of PPS in Step 1 as shown in Example 13 are effective methods to improve the recovery rate.
[0152] [Example 14]
[0153] 33.5 kg of PPS-2 and 200 kg of NMP (each kg of PPS is 100 g of organic polar solvent) were added to a 300 L pressure vessel (I) equipped with a circulation line (I) with a pump and a stirrer, and nitrogen purging was performed. 20 kg of NMP was added to a 70 L pressure vessel (II) equipped with a circulation line (II) with a pump and a stirrer, and nitrogen purging was performed.
[0154] Here, the circulation line (I) is connected to a branch line (I) via a valve, and at the top of the branch line are pressure vessels (I) and (II). Similarly, the circulation line (II) is connected to a branch line (II) via a valve, and at the top of the branch line are pressure vessels (II) and a high-temperature filter (using a PTFE filter with a pore size of 1 μm). A branch line (III) is installed at the inlet of the high-temperature filter, enabling supply to the filter and discharge to other containers. Furthermore, a container (III) is connected to the outlet of the filter.
[0155] The pressure vessel (I) was heated to 50°C, and the pressure vessel (II) was heated to 250°C. The contents of pressure vessel (I) were then continuously supplied to pressure vessel (II) at a rate of 40 kg / hour. Simultaneously, the contents of pressure vessel (II) were continuously withdrawn at a rate of 40 kg / hour. Through this operation, a PAS solution (A) was obtained in pressure vessel (II) (Step 1). In this operation, the pressure in pressure vessel (II) was approximately 0.2 MPa, which was constant. It should be noted that since the supply and withdrawal rates to and from pressure vessel (II) were constant, the amount of contents in pressure vessel (II) could be considered constant during this operation, and the residence time of the contents in pressure vessel (II), i.e., the heating and holding time of the PAS solution (A), was 30 minutes.
[0156] Four hours after the start of this operation, once the PAS solution (A) has been fully displaced and stabilized, it is supplied from branch line (III) to the high-temperature filter to separate the PPS solution (B) from the glass fiber (step 2), obtaining PAS solution (B). The obtained PAS solution (B) is cooled to 150°C to precipitate PPS (step 3). Then, it is added to ion-exchange water and filtered using a filter with a sieve size of 10–16 μm. The resulting filter cake is washed and filtered three times with water at 75°C, and then dried at 120°C to obtain recovered PPS. The recovery rate is determined from the weight of the recovered PPS and the weight of PPS added to PPS-2. Furthermore, the weight-average molecular weight of the recovered PPS and the amount of gas produced are determined using the above method.
[0157] The conditions and characteristics of PPS recycling in the examples are shown in Table 3.
[0158] [Table 3]
[0159]
[0160] Example 14, which uses a continuous operation, has the same recovery rate and gas production volume as Example 8, which uses an intermittent operation. Furthermore, if it becomes a stable operation, the heating time and warming time of step 1 can be shortened, which is excellent from both an LCA (Liquidity, Energy, and Chemical) perspective and a productivity perspective.
[0161] [Reference Example 5]
[0162] After removing the resin part made of PPS resin composition from automotive metal inserts that have been recycled after use in the market, the part is coarsely crushed in a crusher with a long axis dimension of 100 mm or less, washed with water, and then pulverized with a long axis dimension of 10 mm or less to obtain a molded product (PPS-5) of PPS resin composition with oil stains attached.
[0163] The analysis results showed that PPS-5 consisted of 60 wt% PPS and 40 wt% GF, with a weight-average molecular weight of 45,000 for PPS.
[0164] [Reference Example 6]
[0165] After removing the resin part made of PPS resin composition from a housing water supply component that was recycled after use in the market, the component was crushed with water so that the long axis dimension was less than 10 mm, and then washed to obtain a molded product (PPS-6) of the rust-adhered PPS resin composition.
[0166] The analysis results show that PPS-6 is composed of 65% by weight of PPS, 30% by weight of GF, and 5% by weight of olefin copolymer resin, with a weight-average molecular weight of 50,000 for PPS.
[0167] [See Example 7]
[0168] PPS fibers were recovered from bag filters that had been recycled after use in the market and washed with water. PPS fibers (PPS-7) with coal and oil contaminants attached were obtained.
[0169] PPS-7 is composed of approximately 100% PPS, with a weight-average molecular weight of 55,000.
[0170] [Examples 15-23]
[0171] The types of PPS resin compositions or molded articles and the precipitation temperature of step 3 are as shown in Table 4. Otherwise, recycled PPS was obtained by the same operation as in Example 8.
[0172] The conditions and characteristics of PPS recycling in the examples are shown in Table 4.
[0173] [Table 4]
[0174]
[0175] According to Table 4 above, although the resin compositions or molded articles recycled after use in the market contain contaminants from oil, rust, etc., PPS can be recovered with a high recovery rate. Furthermore, by increasing the precipitation temperature in step 3, the separability is improved, and high-quality PPS is obtained.
[0176] [Example 24]
[0177] Instead of PPS-1, PPS (PPS-8) that had been recycled in Example 8 was used. Otherwise, an ISO (1A) dumbbell was produced by the same procedure as in Reference Example 2, and its mechanical properties were compared with those of PPS-2.
[0178] [Table 5]
[0179]
[0180] It is understood that the PPS resin composition obtained by using recycled PPS obtained through the present invention has sufficient weight-average molecular weight, and therefore exhibits the same characteristics as the PPS resin composition obtained by using unused PPS even without repolymerization or other treatments.
[0181] Industry availability
[0182] The PAS recovered by the separation method of the present invention is acceptable from the viewpoint of LCA. It can also be recycled together with the recovered low molecular weight PAS using dihaloaromatic compounds and sulfide compounds as raw materials to repolymerize it into high molecular weight PAS.
[0183] Furthermore, the inorganic and organic filler materials separated and recovered in step 2 of the present invention can also be reused as filler materials for various resin compositions.
[0184] Thus, according to the present invention, PAS and compounding materials can be rationally recycled from the PAS resin composition or its molded articles from the viewpoint of LCA.
Claims
1. A method for separating PAS, wherein the PAS is a polyarylene sulfide, the separation method comprising the following steps 1 to 4. Step 1: A step of heating a PAS resin composition or its molded article in an organic polar solvent to a temperature above 200°C and below 400°C to dissolve PAS and obtain a PAS solution (A), wherein the organic polar solvent is NMP, and NMP is N-methyl-2-pyrrolidone. Step 2: The process of separating PAS solution (A) into solid and liquid components, namely solid and PAS solution (B). Step 3: The PAS solution (B) obtained in Step 2 is cooled to a temperature above 50°C and below 150°C to precipitate PAS. Step 4: A step to separate PAS by performing solid-liquid separation on the mixture obtained in Step 3. in, From step 1 to step 3, solid-liquid separation is achieved by varying the temperature in stages within the same organic polar solvent.
2. The PAS separation method according to claim 1, wherein the PAS resin composition or its molded article in step 1 contains at least one selected from inorganic fillers and organic fillers.
3. The PAS separation method according to claim 1 or 2, wherein the molded article of the PAS resin composition in step 1 is a molded article that has been recycled after being used as an article.
4. The PAS separation method according to claim 1 or 2, wherein the weight-average molecular weight (Mw) of the PAS contained in the PAS resin composition or its molded article before dissolution in step 1 is 10,000 or more and 60,000 or less.
5. The PAS separation method according to claim 1 or 2, wherein some or all of the steps 1 to 4 are performed in a continuous manner.
6. The PAS separation method according to claim 1 or 2, wherein the Mw of PAS contained in the PAS resin composition or its molded article before dissolution in step 1 is reduced to more than 10,000 and less than 60,000 in step 1.
7. The method for separating PAS according to claim 6, wherein in step 1, a sulfur compound is added to the solution.
8. The method for separating PAS according to claim 7, wherein the sulfur compound is at least one compound selected from alkali metal sulfides, alkali metal hydrogen sulfides, and hydrogen sulfide.
9. The PAS separation method according to claim 1 or 2, wherein after step 4, the separated PAS is washed and recovered.
10. A method for manufacturing a PAS resin composition, wherein PAS obtained by the separation method of claim 9 is used as a raw material.
Citation Information
Patent Citations
Production of arylene thioether polymer
JP1992007334A
Method for recovering and reusing fiber from fiber-reinforced plastic
JP1998087872A
Production of polymer blend by recycling high performance polymer
JP1999140221A
Cleaning of filter and filter apparatus
JP1990212529A
Process for recycling polyarylene sulfides
US5994416A